2002
DOI: 10.1093/nar/30.4.950
|View full text |Cite
|
Sign up to set email alerts
|

Non-Watson-Crick interactions between PNA and DNA inhibit the ATPase activity of bacteriophage T4 Dda helicase

Abstract: Peptide nucleic acid (PNA) is a DNA mimic in which the nucleobases are linked by an N-(2-aminoethyl) glycine backbone. Here we report that PNA can interact with single-stranded DNA (ssDNA) in a non-sequence-specific fashion. We observed that a 15mer PNA inhibited the ssDNA-stimulated ATPase activity of a bacteriophage T4 helicase, Dda. Surprisingly, when a fluorescein-labeled 15mer PNA was used in binding studies no interaction was observed between PNA and Dda. However, fluorescence polarization did reveal non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
(54 reference statements)
6
41
0
1
Order By: Relevance
“…Although it is possible to hybridize at initially very high temperatures [15], we prefer to hybridize plasmids at 37 • C in order to avoid increased nicking. Under these conditions we have found that a substantial fraction of PNA interacts with the plasmid in an unspecific way ( Figure 6) and it has also been shown by others that PNA can stack to unrelated DNA in a non-specific manner [19]. This unspecific binding can easily be removed by purifying hybridized plasmids on standard DNA purification spin columns.…”
Section: Visualizing Pna-nucleic Acid Interactionssupporting
confidence: 67%
“…Although it is possible to hybridize at initially very high temperatures [15], we prefer to hybridize plasmids at 37 • C in order to avoid increased nicking. Under these conditions we have found that a substantial fraction of PNA interacts with the plasmid in an unspecific way ( Figure 6) and it has also been shown by others that PNA can stack to unrelated DNA in a non-specific manner [19]. This unspecific binding can easily be removed by purifying hybridized plasmids on standard DNA purification spin columns.…”
Section: Visualizing Pna-nucleic Acid Interactionssupporting
confidence: 67%
“…We cannot exclude that is in part associated with nonspecific cytotoxicity of PNA molecules, as already suggested by other groups. 10,21 Notwithstanding, these results emphasize the essential A peptide carrier for PNA-mediated targeting of cell cycle progression MC Morris et al role of Pep-2 in improving the bioavailability of antisense HypNA-pPNA and PNA molecules and demonstrate the selectivity and specificity of the antisense sequence used in this study.…”
Section: Resultsmentioning
confidence: 51%
“…18 The solubility of PNAs and their tendency to self-aggregate are important factors to be considered for the biological use of PNAs. [21][22][23] PNA solubility is often sequence-dependent, which usually leads to several restrictions in PNA probe design and can be improved by incorporation of Lys residues or ethylene glycol linkers (eg1 ¼ 8 amino-2-6 dioxaoctanoic acid). 18,[21][22][23][24] Efimov et al 25,26 have developed a novel oligonucleotide mimic, a dimeric oligomer that consists of a phosphonate analog of PNA (pPNA) and a PNA-like monomer based on a trans-4-hydroxyl-L-proline (HypNA).…”
Section: Introductionmentioning
confidence: 99%
“…The PNA 14-mer combined excellent specificity and the fastest association rate among the inhibitors tested (Table 1). Its relatively high K i value (12.5 nM) ( Table 1) can be explained by a certain propensity of hydrophobic PNA to self-aggregate (29), which likely reduced the effective concentration of PNA single strands, although we tried to minimize this problem by preparing, handling, and quantifying PNA solutions at 80°C. At explicitly smaller oligomer sizes, however, LNA may become advantageous over PNA.…”
Section: Discussionmentioning
confidence: 99%